Early effects of androgen deprivation on bone and mineral homeostasis in adult men: a prospective cohort study. Issue 2 (August 2020) - Khalil, Rougin; Antonio, Leen; Laurent, Michaël R; David, Karel; Kim, Na Ri; Evenepoel, Pieter; Eisenhauer, Anton; Heuser, Alexander; Cavalier, Etienne; Khosla, Sundeep; Claessens, Frank; Vanderschueren, Dirk; et al.
Abstract : Objective: Long-term androgen deprivation therapy (ADT) negatively influences bone. The short-term effects on bone and mineral homeostasis are less known. Therefore, we aimed to investigate the early effects of ADT on calcium/phosphate homeostasis and bone turnover. Design: Prospective cohort study. Methods: Eugonadal adult, male sex offenders, who were referred for ADT to the endocrine outpatient clinic, received cyproterone acetate. Changes in blood markers of calcium/phosphate homeostasis and bone turnover between baseline and first follow-up visit were studied. Results: Of 26 screened patients, 17 were included. The median age was 44 (range 20–75) years. The median time interval between baseline and first follow-up was 13 (6–27) weeks. Compared to baseline, an 81% decrease was observed for median total testosterone (to 3.4 nmol/L (0.4–12.2); P  < 0.0001) and free testosterone (to 0.06 nmol/L (0.01–0.18); P  < 0.0001). Median total estradiol decreased by 71% (to 17.6 pmol/L (4.7–35.6); P  < 0.0001). Increased serum calcium ( P  < 0.0001) and phosphate ( P  = 0.0016) was observed, paralleled by decreased PTH ( P  = 0.0156) and 1, 25-dihydroxyvitamin D3 ( P  = 0.0134). The stable calcium isotope ratio (δ 44/42 Ca) decreased ( P  = 0.0458), indicating net calcium loss from bone. Bone-specific alkaline phosphatase and osteocalcin decreased ( P  < 0.0001 and P  = 0.0056, respectively), periostin tended to decrease ( P  = 0.0500), whereas sclerostin increased ( P  < 0.0001), indicating suppressed bone formation. Serum bone resorption markers (TRAP, CTX) were unaltered. Conclusions: In adult men, calcium release from the skeleton occurs early following sex steroid deprivation, reflecting early bone resorption. The increase of sclerostin and reduction of bone formation markers, without changes in resorption markers, suggests a dominant negative effect on bone formation in the acute phase.